Peningkatan Prestasi Belajar Materi Teks Eksposisi Melalui Model Think Pair and Share Peserta Didik Kelas VII D Di SMP Negeri 2 Panggul Trenggalek - Kusmini, Kusmini (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to improve student learning outcomes in Exposition Text Material with Think Pair Share in students of class VII D Semester 1 at SMP Negeri 2 Panggul Trenggalek. This research is qualitative descriptive research the type of Class Action Research will be presented in the form of a cycle. Each cycle consists of four stages, namely (1) planning. (2) implementation or action, (3) observation, (4) reflection. The study used one instrument: a test. Test instruments are used to collect achievement data. The results of this study in cycle I that students who completed learning as much as 47.82%. The completion has not reached at least 80%. Learners who follow learning with good results as many as 9 people (27.27%). Learning achievement of learners in cycle I has not achieved classical completion. Students who completed learning as much as 47.82%. The completion has not reached at least 80%. Learners who follow learning with good results as many as 9 people (27.27%). In cycle II this is good because it has reached completion. Students who completed learning as many as 20 people with a percentage of (87%). The completion of classical learning has reached a minimum of 80%. Learners who have minimal results are good in learning as many as 20 people (87%). Thus it can be stated that cooperative learning model Think Pair Share with Material Exposition material takes place actively, creatively, effectively, and pleasantly. Learning in Cycle II has been successful because minimal completion can be achieved. The success of Cycle II is characterized by a complete completion of 87%.